“Saucy Stink”: Smells, Sanitation, and Conflict in Early Modern London - Logue, Alexandra (Renaissance and Reformation / Renaissance et Réforme, 2021)
This article examines olfactory offenses in early modern London. It explores how inhabitants managed causes of malodorous air, focusing on common nuisances stemming from everyday household practices like laundry and waste management. Clotheslines were hung up between lodgings, households disposed of kitchen waste in gutters overflowing with garbage, and neighbours used stinking, communal privies. Seasonal weather intensified the city’s poor air quality, and rainwater washed refuse into urban rivers. In the early seventeenth century, the growing awareness of the effects of air quality on health coincided with significant demographic changes in the city. Insalubrious air was intrinsically linked to increased migration, overcrowded neighbourhoods, and the spread of diseases. The improvement of the city’s air quality became a more immediate concern for Londoners, civic authorities, and the early Stuart monarchs, who deployed a range of sanitation strategies. As London grew, so too did concern for its inhabitants and the dwellings they occupied.